The fingerprint identification of attendance analysis & management - Lee, Guan Heng (Universiti Malaysia Sarawak, UNIMAS, 2005)
The Fingerprint Attendance Management System (FAMAS) is a student attendance management system for university applied with fingerprint technology. The system is able to manage the student daily attendance. There are five major modules implemented in this system which is Student Information Module, Subject Information Module, Subject Registration Module, Attendance Management Module, and Attendance Report Module. In Student Information Module, it is allows to add, edit and delete student information with navigation and search features. Administrator/lecturer can add, edit and delete subject information in Subject Information Module. This module is used to allow administrator select a class in attendance management module. For convenience purpose, Subject Registration Module was implemented to allow student register available subject in the system. With this feature, administrator can view the list of students who are taken the particular subject. Attendance Management Module is a module where the students’ attendance has been recorded. The fingerprint technology is applied in this module that captured and template of fingerprint from database is compare. There is a checking attendance status feature in this module who is request from students for know their currently attendance status. Besides, reporting the students’ attendance records has been implemented in Attendance Report Module. Administrator can print out the each class attendance report or export it into html format for future checking purpose.